2005
DOI: 10.1021/cm050110a
|View full text |Cite
|
Sign up to set email alerts
|

Monodispersed InP Quantum Dots Prepared by Colloidal Chemistry in a Noncoordinating Solvent

Abstract: III−V semiconductor quantum dots are of considerable interest as their applications cover a broad spectrum, from optoelectronic to biomedical technology. For them to be of practical value, there is a need for a method that provides rapid and scalable production of highly monodispersed nanoparticles. This paper reports an efficient and rapid method of producing highly monodispersed InP quantum dots using a novel precursor-based colloidal synthesis in a noncoordinating solvent. The method also allows judicious c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
127
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(137 citation statements)
references
References 40 publications
(68 reference statements)
10
127
0
Order By: Relevance
“…[10,11] Their PL spectra contain two emission bands: one at the band edge and a second broader band at longer wavelengths (lower energies), showing the similar feature to those InP NCs prepared using the traditional TOPO method. [5,6,9,13] According to the previous investigations on the both bands, [5,6,9,13,23] the high-energy band is assigned to band-edge recombination and the low-energy band to recombination of surface states.…”
mentioning
confidence: 65%
See 2 more Smart Citations
“…[10,11] Their PL spectra contain two emission bands: one at the band edge and a second broader band at longer wavelengths (lower energies), showing the similar feature to those InP NCs prepared using the traditional TOPO method. [5,6,9,13] According to the previous investigations on the both bands, [5,6,9,13,23] the high-energy band is assigned to band-edge recombination and the low-energy band to recombination of surface states.…”
mentioning
confidence: 65%
“…It is generally believed that such low PL efficiency is due to inadequate passivation of the NC surface. [5,9,11,13] Previous studies have shown that the PL efficiency of InP NCs could be drastically improved by photochemical etching of the NC surface with HF. [5,9,11,13] We thus treated our InP samples with a solution of HF through a modification of the standard method.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, these were found to be potentially promising building blocks for the optoelectronic devices. Up until 2009, the SLS growth of InP NWs was primarily focused on the use of phosphines or organo-indium complexes containing one or more legating phosphines as precursors [70][71][72][73][74]. The most commonly used phosphine precursor was tris-trimethylsilylphosphine that is intrinsically highly toxic and pyrolytic that is detrimental to the process of scaling up preparation and subsequent mass production of InP NWs essential for economic device fabrication.…”
Section: (C) Solution-liquid-solid Synthesismentioning
confidence: 99%
“…The presence of two peaks near 132.9 and 129.3 eV were very much similar to previous results reported for InP QDs. 16 It has been already reported by Guzelian that the peak near 129.3 eV is due to phosphorous from InP QDs, and that the peak near 132.9 eV is due mainly to oxidized phosphorous. 5(d) Figure 8(c) shows the high-resolution spectrum of In 3d region.…”
mentioning
confidence: 92%